Human capital investment: an analysis of the return of higher education - Dina Hadia; Nasri Bachtiar; Elfindri Elfindri (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
This study is aimed to analyze particular problems related to economic return for West Sumateran workers who graduated higher education by using human capital investment concepts. The dataset is sourced from National Labor Force Survey for West Sumatera 2017 and contains 1798 records of those aging at least 15 years, graduating from academy, university and postgraduate schools and distributed in all main industries. The return to higher education is estimated using Mincerian framework by considering modulatory effects of college major graduated. Other worker characteristics including training and experience are used to measure earning differentials among worker. The result of this study shows that the return to higher education is significantly positive and amplified if workers graduated from certain college majors. It is also found that participating in job training and having working experience prior to current job significantly increase highly educated workers earning in West Sumatera.